Differences in anthropometric and morphological characteristics, as well as motor abilities, between boys and girls aged thirteen to fifteen. - Adis Bekrić,; Ilma Tutnjić,; Adis Tabaković,; Ekrem Čolakhodžić,; Almir Atiković, (Sport Scientific And Practical Aspects, 2025)
This paper aims to determine whether there is a difference in anthropometric, morphological characteristics, and motor abilities, between boys and girls at the age of 13-15 years. The study included 95 subjects of which 49 were boys (51.6%) and 46 girls (48.4%), with mean age girls 14.14 and boys 14.40 years. The sample comprised students who belong to the urban area of the City of Tešanjka. The sample of variables in this study consisted of 15 tests of motor abilities and 10 morphological characteristics (body height, body mass, body mass index, etc.). This paper aims to determine whether there are differences in anthropometric characteristics and motor abilities between boys and girls aged 13-15 years. The results obtained in this study were compared with those of previous research, and the conclusions reached through a summary analysis were explained. Boys were taller and heavier at the age of 14. The results show that boys achieved statistically better results in most tests compared to girls of the same age.